A lipid nanoparticle-based oligodendrocyte-specific mRNA therapy - Sawamura, Masanori; Tachikawa, Kiyoshi; Hikawa, Rie; Akiyama, Hisako; Kaji, Seiji; Yasuda, Ken; Leu, Angel I.; Hong, Hyojung; Mukthavaram, Rajesh; Chivukula, Pad; Yamakado, Hodaka; Hirabayashi, Yoshio; et al. (Molecular therapy. Nucleic acids, 2024)
Despite the wide range of applications of mRNA therapies, major difficulties exist in the efficient delivery of mRNA into oligodendrocytes, a type of glial cell in the brain. Commonly used viral vectors are not efficient in transforming oligodendrocytes. In this study, we introduced mRNAs into oligodendrocytes with high efficiency and specificity using LUNAR lipid nanoparticles. The uptake of LUNAR lipid nanoparticles occurred via low-density lipoprotein receptors in the presence of apoprotein E. A single dose of LUNAR-human galactosylceramidase mRNA significantly improved phenotypes and survival of twitcher mice, a mouse model of Krabbe disease wherein oligodendrocytes are damaged by galactosylceramidase deficiency. This approach to mRNA therapeutics, combined with cell-specific nanocarriers, demonstrates remarkable potential for the treatment of neurological disorders associated with oligodendrocytes. [Display omitted] Matsuzawa and colleagues reported that LUNAR lipid nanoparticles (LNPs) effectively and specifically introduced mRNA into oligodendrocytes, and LUNAR-human GALC mRNA improved phenotype and survival in a mouse model of Krabbe disease. New drug delivery systems that target specific cell types in the brain have great potential as new mRNA therapies.